2018
DOI: 10.1002/jia2.25079
|View full text |Cite
|
Sign up to set email alerts
|

Peer counselling versus standard‐of‐care on reducing high‐risk behaviours among newly diagnosed HIV‐positive men who have sex with men in Beijing, China: a randomized intervention study

Abstract: IntroductionReducing high‐risk behaviours (i.e. multiple partnership, condomless anal/vaginal sex, alcohol use before sex, illicit drug use) after HIV diagnosis is critical for curtailing HIV transmission. We designed an intervention to explore peer‐ counselling in reducing high‐risk behaviours among newly diagnosed HIV‐positive Chinese men who have sex with men (MSM).MethodsWe randomized 367 newly diagnosed HIV‐positive men to either standard‐of‐care (SOC; n = 183) or peer‐counselling intervention (n = 184), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 49 publications
0
43
0
1
Order By: Relevance
“…Ten studies generated [17,20,29,42,43,46,55,[57][58][59] 11 independent effect sizes on unprotected sex with a combined study population of 6289. Four of the articles showed a significant reduction in unprotected sex, while four of the articles showed a non-significant reduction.…”
Section: Unprotected Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies generated [17,20,29,42,43,46,55,[57][58][59] 11 independent effect sizes on unprotected sex with a combined study population of 6289. Four of the articles showed a significant reduction in unprotected sex, while four of the articles showed a non-significant reduction.…”
Section: Unprotected Sexmentioning
confidence: 99%
“…Previous studies have shown that peer education could reduce risk behaviors [15,16] and promote health [17][18][19][20][21], but some researchers measured the influence of peer-based intervention on conversations about HIV prevention and highlighted the effect declined and the frequency of conversations on the topics decreased [22]. Previous meta-analyses only synthesized the effect of peer education in developing countries in general population [8] and only revealed the effect of peer education on condom use [17] or HIV testing [23] among MSM groups. What's more, it is also still unclear whether peer education can bring about positive effects and maintain the changes consistently among different high risk HIV groups both in developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…The data for this analysis were from the baseline surveys of a randomized clinical trial called the China MP3 Project. This project had two study phases and was described in detail elsewhere [32]. In brief, men who lived in Beijing, self reported having sex with another man, were 18 years or older and willing to provide written informed consent were recruited (via short message service, website advertisement, gay-frequented venue outreach and peer referral) and tested for HIV in the Phase I and completed a cross-sectional survey.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Self-discrimination could lead to high-risk sexual behaviors. [30,31] Multiple comprehensive HIV intervention programs have been implemented targeting Chinese MSM in recent years, including treatment of HIV/STIs and provision of pre-exposure prophylaxis, [3234] but these programs often lacked of psychological counseling on acceptance of their sexual identity among MSM.…”
Section: Discussionmentioning
confidence: 99%